2019
DOI: 10.3390/sci1020048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dissolution Enhancement of Aprepitant Drug in Ternary Pharmaceutical Solid Dispersions with Soluplus® and Poloxamer 188 Prepared by Melt Mixing

Abstract: In the present study Aprepitant (APT) ternary solid dispersions (SDs) were developed and evaluated for the first time. Specifically, ternary SDs of APT with Poloxamer 188 and Soluplus® (SOL) were prepared via melt mixing and compared to binary APT/Poloxamer 188 and APT/SOL SDs. Initially, combined thermo-gravimetric and hot-stage polarized light microscopy studies indicated that all tested compounds were thermally stable up to 280 °C, while Poloxamer 188 acted as a plasticizer to SOL by significantly reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…Thermogravimetric analysis revealed that the MNP contents in the dry electrospun products of formulations F e 4 and F w 2 were (50.5 ± 0.3) % (w/w) and (50.9 ± 0.5) % (w/w), respectively. The MNP content in the dry electrospun product was determined based on the fact that both polymers, namely PEO and P188, undergo complete thermal decomposition in the temperature range from 400 to 500 • C (Gordon Cameron et al, 1989;Nanaki et al, 2019), whereas the MNPs are not susceptible to thermal decomposition in this temperature range. As the theoretical content of MNPs in the dry product was 50 % (w/w), the thermogravimetric analysis confirmed that MNPs were incorporated in the dry product without any loss.…”
Section: Throughout Evaluation Of the Final Formulationsmentioning
confidence: 99%
“…Thermogravimetric analysis revealed that the MNP contents in the dry electrospun products of formulations F e 4 and F w 2 were (50.5 ± 0.3) % (w/w) and (50.9 ± 0.5) % (w/w), respectively. The MNP content in the dry electrospun product was determined based on the fact that both polymers, namely PEO and P188, undergo complete thermal decomposition in the temperature range from 400 to 500 • C (Gordon Cameron et al, 1989;Nanaki et al, 2019), whereas the MNPs are not susceptible to thermal decomposition in this temperature range. As the theoretical content of MNPs in the dry product was 50 % (w/w), the thermogravimetric analysis confirmed that MNPs were incorporated in the dry product without any loss.…”
Section: Throughout Evaluation Of the Final Formulationsmentioning
confidence: 99%
“…The initiation of xylitol thermal decomposition was observed at 200 °C and total weight loss recorded at 300 °C ( Figure 3 A) [ 75 ]. Both methylcellulose and Kolliphor ® showed their final thermal decomposition at temperatures greater than 400 °C with an onset of thermal events only displayed at higher heat levels (i.e., 300 °C and 330 °C, respectively) ( Figure 3 D,E)) [ 76 , 77 ]. The onset of thermal decomposition for Primellose ® , polyvinylpyrrolidone, magnesium stearate, potassium chloride and sodium chloride were noted at 258 °C, 360 °C, 87 °C, 340 °C, and 400 °C, respectively while their final decomposition were recorded at temperatures of 600 °C and above ( Figure 3 B,C,F–H) showing their high resistance to thermal deformation as separate entities.…”
Section: Resultsmentioning
confidence: 99%
“…In TGA analysis, it was observed that the solid dispersions prepared with MLBG polymer showed minor fluctuations in mass loss, indicating increased thermal stability of dispersion at higher temperature when the percentage of mass loss were compared among both optimized dispersions, which might be due to interactions. TGA thermograms of BEX-polymer systems, indicated that the presence of BEX has minimal effect on the thermal profile of the polymeric carriers, a characteristic that strongly implies a favorable interface between drug and polymers [59][60][61].…”
Section: Discussionmentioning
confidence: 99%